Aging-related features predict prognosis and immunotherapy efficacy in hepatocellular carcinoma - Hong, Ting; Su, Wei; Pan, Yitong; Tian, Chenxi; Lei, Guang (Frontiers in Immunology, 2022)
Aging microenvironment serves important roles in cancers. However, most studies focus on circumscribed hot spots such as immunity and metabolism and so on. Thus, it is well ignored that the aging microenvironment contributes to the proliferation of tumor. Herein, we established three prognosis-distinctive aging microenvironment subtypes, including AME1, AME2 and AME3, based on aging-related genes and characterized them with "Immune Exclusion", "Immune Infiltration", and "Immune Intermediate" features separately. AME2 subtype tumors were characterized by specific activation of immune cells, and were most likely to be sensitive to immunotherapy. AME1 subtype tumors were characterized by inhibition of immune cells with high proportion of Catenin Beta 1(CTNNB1) mutation, which was more likely to be insensitive to immunotherapy. Furthermore, we found that CTNNB1 may inhibit the expression of C-C Motif Chemokine Ligand 19 (CCL19), thus restraining the immune cells and attenuating the sensitivity of immunotherapy. Finally, we also established a robust aging prognostic model to predict the prognosis of patients with hepatocellular carcinoma. Overall, this research promotes a comprehensive understanding about aging microenvironment and immunity in hepatocellular carcinoma and may provide potential therapeutic targets for immunotherapy.